2019
DOI: 10.5093/jwop2019a11
|View full text |Cite
|
Sign up to set email alerts
|

The Journey from Likert to Forced-Choice Questionnaires: Evidence of the Invariance of Item Parameters

Abstract: Several meta-analyses have shown that the Five-Factor Model of personality predicts a wide range of performance outcomes in the workplace and is a useful framework for organizing most personality measures (see, e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 36 publications
1
25
0
2
Order By: Relevance
“…The absolute values for the loadings in the FCQ were systematically lower than the ones for the GSQ (0.37 vs. 0.56). These results are consistent with the findings of Morillo et al (2019) on the invariance of discrimination parameters under the GRM and the MUPP-2PL models.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The absolute values for the loadings in the FCQ were systematically lower than the ones for the GSQ (0.37 vs. 0.56). These results are consistent with the findings of Morillo et al (2019) on the invariance of discrimination parameters under the GRM and the MUPP-2PL models.…”
Section: Resultssupporting
confidence: 92%
“…The items in the pool have been previously applied to a 5-point Likert scale format to a total of 1531 Psychology undergraduate students at Universidad Autónoma de Madrid, using an incomplete sampling design, and were calibrated under Samejima’s Graded Response Model (GRM; Samejima, 1968). Partial reports on the calibration study can be found in Nieto et al (2017) and Morillo et al (2019). In the calibration study conducted by Nieto et al (2017), the scores based on this item pool showed good convergent validities with the NEO Five-Factor Inventory-3 (McCrae and Costa, 2007), which is a brief 60-items version of the NEO Personality Inventory-3 (McCrae et al, 2005).…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…It is known that forced-choice inventories, especially quasi-ipsative tests, are a preferable option when it comes to control faking or social desirability [ 57 61 ]. Furthermore, quasi-ipsative personality inventories have shown a similar or a better predictive validity than personality tests with other formats in the prediction of important criteria in both occupational and educational contexts [ 62 64 ]. In the study of CAB, only Cuadrado et al [ 50 ] have analyzed this question using a quasi-ipsative questionnaire for higher education students.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Salgado et al (2019) revisit a current construct in the prediction of professional performance: subjective well-being (SWB). In an extraordinary effort, the authors develop a four-year longitudinal study in which they relate the cognitive and emotional components of SWB with job performance.…”
Section: Assessment Of New Constructs In the Recruitment And Selectiomentioning
confidence: 99%